2015
DOI: 10.1016/j.cell.2015.04.024
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Immune Receptor Detects Pathogen Effectors that Target WRKY Transcription Factors

Abstract: Defense against pathogens in multicellular eukaryotes depends on intracellular immune receptors, yet surveillance by these receptors is poorly understood. Several plant nucleotide-binding, leucine-rich repeat (NB-LRR) immune receptors carry fusions with other protein domains. The Arabidopsis RRS1-R NB-LRR protein carries a C-terminal WRKY DNA binding domain and forms a receptor complex with RPS4, another NB-LRR protein. This complex detects the bacterial effectors AvrRps4 or PopP2 and then activates defense. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
507
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(531 citation statements)
references
References 53 publications
15
507
2
7
Order By: Relevance
“…The first experimental evidence was provided by the investigation of the rice blast resistance NLR pairs RGA4/RGA5 and Pik‐1/Pik‐2 and important validation was supplied by detailed analysis of the A. thaliana NLR pair RPS4/RRS1 (Kanzaki et al ., 2012; Cesari et al ., 2013; Le Roux et al ., 2015; Sarris et al ., 2015). The occurrence of NLRs with decoy domains in phylogenetically unrelated immune receptors from monocot and dicot plants suggested that it is a widespread phenomenon and the first large‐scale analysis showed that the integration of unusual domains is frequent among cloned R proteins of the NLR class and RGA homologs similar to RGA5 and RRS1 (Césari et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first experimental evidence was provided by the investigation of the rice blast resistance NLR pairs RGA4/RGA5 and Pik‐1/Pik‐2 and important validation was supplied by detailed analysis of the A. thaliana NLR pair RPS4/RRS1 (Kanzaki et al ., 2012; Cesari et al ., 2013; Le Roux et al ., 2015; Sarris et al ., 2015). The occurrence of NLRs with decoy domains in phylogenetically unrelated immune receptors from monocot and dicot plants suggested that it is a widespread phenomenon and the first large‐scale analysis showed that the integration of unusual domains is frequent among cloned R proteins of the NLR class and RGA homologs similar to RGA5 and RRS1 (Césari et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The RATX1/HMA domain in the rice R proteins RGA5 and Pik‐1, which resembles the product of the blast susceptibility gene Pi21 , interacts physically with and confers specificity to the Magnaporthe oryzae effectors AVR‐Pia and AVR‐Pik (Kanzaki et al ., 2012; Cesari et al ., 2013; Césari et al ., 2014). Recent studies on the Arabidopsis thaliana NLR RRS1 also came to the conclusion that the WRKY domain integrated into RRS1 acts as an integrated decoy that recognizes the effectors AvrRps4 and PopP2 by monitoring the perturbation they induce in WRKY transcription factors that are major regulators of plant defense (Le Roux et al ., 2015; Sarris et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Single fusions were found for a RNA polymerase 3, DUF659, a protein tyrosine phosphatase domain and several other domains (Supplementary Table 4). Despite capturing long flanking sequences, we could not find any inverted paired NLRs [18][19][20] . The phylogenetic tree of SP2271 NLRs (Figure 2), constructed from the NB-ARC domains of complete NLRs (Supplementary Files 3-5), shows a Solanaceae typical structure, including a TIR-NLR to CC-NLR ratio of 1:4.7, opposite to that found in Brassicaceae 4 .…”
mentioning
confidence: 85%
“…sp. lycopersici, V. dahliae, Phytophthora parasitica and P. sojae (Novo et al, 2006;Wu et al, 2008;Poueymiro and Genin, 2009;Maruthachalam et al, 2011;Ma et al, 2015;Bravo Ruiz et al, 2016). These studies conclude that CWDEs are important for virulence.…”
Section: Effectors With Apoplastic Functionsmentioning
confidence: 99%
“…The acetyltransferase PopP2 (RipP2) from R. solanacearum localizes to the plant cell nucleus and directly acetylates lysine residues in the WRKYGQK DNA-binding motif of WRKY transcription factors (Deslandes et al, 2003;Le Roux et al, 2015;Sarris et al, 2015). Acetylation by PopP2 interferes with the DNA binding of WRKY transcription factors and thus with the transcriptional activation of WRKY transcription factor-regulated immune genes, leading to enhanced virulence (Le Roux et al, 2015;Sarris et al, 2015).…”
Section: Effectors With Cytoplasmic Functionsmentioning
confidence: 99%